Multicultural Cities. - Nelson, Jacqueline; Ho, Christina (Palgrave Macmillan, 2020)
The presence of Aboriginal Australians, colonising settlers and their descendants, migrants from a wide range of countries of origin and refugees seeking asylum in Australia has resulted in cities that have highly diverse populations. This chapter opens with a brief historical overview of key moments that have shaped Australia’s multicultural cities. Contested and dynamic understandings of multiculturalism are highlighted. The second part of the chapter looks at the geography of cultural difference in multicultural cities, exploring debates about ‘ghettos’ and ethnic residential concentration, ethnic tensions over use of space and policy initiatives to enhance urban intercultural relations. The last part of the chapter draws together some critical approaches to multicultural cities, including debates about the politics of difference, ‘everyday multiculturalism’ and the concept of ‘cosmo-multiculturalism’.
Keywords: Multikultur; Vielfalt; Segregation; Stadtteil; Ghetto